Класифікація зображень на основі квантування ознак - Мазур, Є. В. (ХНУРЕ, 2025)
The results of an experimental study of a highspeed image classification method that performs classification using cluster representation weights for a reference database are presented. The BRISK detector was used to obtain keypoint descriptors. Offline and online versions of the classifier were developed. The results showed a significant acceleration of classification compared to the traditional method based on linear search.
Keywords: класифікація зображень; квантування ознак